Interference of Obesity in Chemotherapy for Women with Breast Cancer - Kirjner, Aline (2007)
Breast cancer currently occupies a key position in the scientific literature due to its increasing incidence and high mortality rate, especially in Western women. Chemotherapy is one of the feasible treatment modalities for the disease, and a correct estimate of drug doses is necessary. Various algorithms are capable of predicting chemotherapy doses, based on different parameters such as current body weight and body surface. Some oncologists apply an empirical dose reduction for obese patients on grounds of a possible exacerbation in toxicity, while others maintain the full doses. It is speculated that obesity may play an important role in the metabolism of cytotoxic drugs and may influence their pharmacokinetics, thereby interfering in the treatment outcome. There is still no consensus as to the ideal dosage for obese patients. Research has shown that obesity can interfere directly and/or indirectly in chemotherapy for women with breast cancer, thus emphasizing the need for additional studies in search of appropriate answers.